O projeto científico de Goethe: subjetividade, unidade e arte como alternativa à concepção utilitarista moderna de ciência - Belmonte , Leonardo Henrique (2020)
This research aims to understand Goethe’s scientific thinking as an alternative to the maxims of the modern science. Between the sixteenth and nineteenth centuries, the Western world underwent significant changes in science. The so-called Scientific Revolution happened, and with it the way that scholars viewed and conceived nature and science was rethought. Studies done by Copernicus, Kepler, Galileo and Newton on the cosmos illustrate how nature was mathematized, giving science a functional and mechanical aspect. Furthermore, Bacon and Descartes philosophically define how modern science should behave: through a utilitarian, objective and rational method, separating the primary and secondary qualities, which resulted in subject-object dichotomy. Thus, the subjectivity becomes secondary and uninteresting to science. Johann Wolfgang von Goethe (1749-1832) is best known as a poet and literary writer, but he also writes numerous works and researches in the field of the natural sciences. In 1790 he releases “Metamorphosis of Plants” and in 1810 he publishes “Theory of Colours”, such works intrinsically carry Goethe’s method and his scientific conceptions. The author bases his thinking on a holistic perception of nature in its totality; God and nature as unity, and man as part of this wholeness. Goethe’s works illustrate how he unifies science, subjectivity and art in the same conception of dynamic totality. For being part of the same entirety, the subject is not separated from the object. Considering that science should study the forms and their moves within the wholeness, Goethe creates Morphology. The Goethean way of knowing the natural sciences is shown as an alternative, a different path to understand the organic world. When investigating the importance of the subjective for science, Goethe’s empiricism does not separate subject and object while qualitatively reframes the studies of the natural sciences.